Pyrrolo[3, 2‐b]pyrrole as the Central Core of the Electron Donor for Solution‐Processed Organic Solar Cells. Issue 7 (11th May 2017) - Domínguez, Rocío; Montcada, Núria F.; de la Cruz, Pilar; Palomares, Emilio; Langa, Fernando
Abstract: A series of three small‐molecule acceptor–donor–acceptor (A‐D‐A) compounds with a tetraaryl‐1, 4‐dihydropyrrolo[3, 2‐ b ]pyrrole as the central building block were synthesized and fully characterized. These molecules present high thermal stability and suitable HOMO–LUMO energy levels making them feasible electron‐donor materials in bulk heterojunction organic solar cells (BHJ‐OSC). Moreover, theoretical work predicts of a lack of planarity and no π–π stacking, furthermore. The electron density of the HOMO is distributed on the pyrrole–pyrrole moiety and that of the LUMO is delocalized, in contrast, on the phenyl groups. The organic solar cells deliver an open‐circuit voltage of 0.99 V. However, the overall efficiency is limited due to the low charge mobility measured for holes, 10 −9 cm 2 V −1 s −1 . Abstract : Small molecules for organic solar cells : Three new small‐molecule acceptor–donor–acceptor (A‐D‐A) compounds with a tetraaryl‐1, 4‐dihydropyrrolo[3, 2‐ b ]pyrrole as the central building block have been synthesized and fully characterized. These molecules present high thermal stability and suitable HOMO–LUMO energy levels. The bulk heterojunction organic solar cells deliver an open‐circuit voltage of 0.99 V.